Transatlantic "airscapes" : a seaplane's shadow in a rain-circle - Davis, G. H.
Two colour illustrations depicting meteorological phenomena encountered by the crew of the Friendship during its transatlantic flight from Newfoundland to Ireland in 1928: a rain circle and a fog bank. The plane carried Amelia Earhart as a passenger, who later described these sights to illustrator G.H. Davis. Periodical covers have been included with many of the digitized articles whether they relate to them or not. Extra pages not part of the article in question may also be present.